2019
DOI: 10.18502/kss.v3i26.5424
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Good Corporate Governance and Its Implications on Organizational Commitments (Empirical Study on Employees of Government-Owned Islamic Banks in Dki Jakarta Province)

Abstract: The purpose of this research was to determine the effect of leadership, competence, organizational culture and Good Corporate Governance partially or simultaneously on organizational commitment.. Based on the results of the research, the findings are as follows: leadership, compensation, and organizational culture partially or simultaneously significant effect on good corporate governance with a contribution of 69%. Partially, the organizational culture reflected by ikhwana culture (friendship) has a positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…This study also found that effective commitment plays a vital role as mediators in GCG and KM effect on professional performance. This evidence in line with studies concluded that GCG influences affective commitment [56] [57], KM influences affective commitment [58]- [61], and affective commitment affects professional performance [47]- [55]. This finding reveals empirical facts that the existence of affective commitment is very important to be considered in the context of increasing professional performance through GCG and KM.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This study also found that effective commitment plays a vital role as mediators in GCG and KM effect on professional performance. This evidence in line with studies concluded that GCG influences affective commitment [56] [57], KM influences affective commitment [58]- [61], and affective commitment affects professional performance [47]- [55]. This finding reveals empirical facts that the existence of affective commitment is very important to be considered in the context of increasing professional performance through GCG and KM.…”
Section: Discussionsupporting
confidence: 88%
“…The principles of KM, which concern the people, process, and concept, can be excellence conditioned to potentially increase affective commitment, which involves the employee's emotional attachment to, identification with, and involvement in the organization [46]. The studies conducted by scholars in various contexts and organizations also indicated that KM affects affective commitment [58]- [61]. Based on the statements and reviews above, the fifth hypothesis in this study is: H 5 : KM had a direct effect on affective commitment…”
Section: Km and Affective Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were in line, consistent, and confirmed other studies and research results used as a reference to develop this research hypothesis. For example, several studies in multiple contexts and fields concluded that affective commitment is influenced by PVL (e.i., Dhammika, 2016;Wu & Chen, 2018) and SOC (e.g., Acar, 2012;Aini & Maswanto, 2019). As a consequence of this evidence, school principals urgently applied PVL intensively and manage SOC conductively more through various policies, approaches, and strategies that can rely on to enhance teachers' affective commitment.…”
Section: Resultsmentioning
confidence: 99%
“…That it then implicates enhancing teachers' affective commitment, reflected in an identification with the organization and involvement in the organization activities (Meyer & Allen, 1991; Newstrom, 2017; Ivancevich, Konopaske, & Matteson, 2018). The studies carried out by Sarwono, Jusuf, and Sumarto (2020) also indicate that PVL affects SOC; meanwhile, the research conducted by Aini and Maswanto (2019) shows that SOC influences affective commitment. Based on argues and research result above, can formulate the hypotheses: H4: PVL had an indirect effect on affective commitment mediating by SOC.…”
Section: Pvl and Affective Commitment Mediating By Socmentioning
confidence: 95%